Beneficial Renal and Pancreatic Phenotypes in a Mouse Deficient in FXYD2 Regulatory Subunit of Na,K-ATPase - Arystarkhova, Elena (Frontiers in Physiology, 2016)
The fundamental role of Na,K-ATPase in eukaryotic cells calls for complex and efficient regulation of its activity. Besides alterations in gene expression and trafficking, kinetic properties of the pump are modulated by reversible association with single span membrane proteins, the FXYDs. Seven members of the family are expressed in a tissue-specific manner, affecting pump kinetics in all possible permutations. This mini-review focuses on functional properties of FXYD2 studied in transfected cells, and on noteworthy and unexpected phenotypes discovered in a Fxyd2-/- mouse. FXYD2, the gamma subunit, reduces activity of Na,K-ATPase either by decreasing affinity for Na+, or reducing Vmax. FXYD2 mRNA splicing and editing provide another layer for regulation of Na,K-ATPase. In kidney of knockouts, there was elevated activity for Na,K-ATPase and for NCC and NKCC2 apical sodium transporters. That should lead to sodium retention and hypertension, however, the mice were in sodium balance and normotensive. Adult Fxyd2-/- mice also exhibited a mild pancreatic phenotype with enhanced glucose tolerance, elevation of circulating insulin, but no insulin resistance. There was an increase in beta cell proliferation and beta cell mass that correlated with activation of the PI3K-Akt pathway. The Fxyd2-/- mice are thus in a highly desirable state: the animals are resistant to Na+ retention, and showed improved glucose control, i.e. they display favorable metabolic adaptations to protect against development of salt-sensitive hypertension and diabetes. Investigation of the mechanisms of these adaptations in the mouse has the potential to unveil a novel therapeutic FXYD2-dependent strategy.